Relationship between type 2 diabetes mellitus and markers of cutaneous melanoma aggressiveness: an observational multicentric study in 443 patients with melanoma. (1st October 2021) - Nagore, E.; Martinez‐Garcia, M.A.; Gomez‐Olivas, J.D.; Manrique‐Silva, E.; Martorell, A.; Bañuls, J.; Carrera, C.; Ortiz, P.; Gardeazabal, J.; Boada, A.; de Eusebio, E.; Chiner, E.; et al.
Summary: Background: Some studies have suggested a relationship between type 2 diabetes mellitus (T2DM) and increased incidence of melanoma. Efforts are under way to identify preventable and treatable factors associated with greater melanoma aggressiveness, but no studies to date have examined the relationship between T2DM and the aggressiveness of cutaneous melanoma at diagnosis. Objectives: To explore potential associations between T2DM, glycaemic control and metformin treatment and the aggressiveness of cutaneous melanoma. Methods: We conducted a cross‐sectional multicentric study in 443 patients diagnosed with cutaneous melanoma. At diagnosis, all patients completed a standardized protocol, and a fasting blood sample was extracted to analyse their glucose levels, glycated haemoglobin concentration and markers of systemic inflammation. Melanoma characteristics and aggressiveness factors [Breslow thickness, ulceration, tumour mitotic rate (TMR), sentinel lymph node (SLN) involvement and tumour stage] were also recorded. Results: The mean (SD) age of the patients was 55·98 (15·3) years and 50·6% were male. The median Breslow thickness was 0·85 mm. In total, 48 (10·8%) patients were diagnosed with T2DM and this finding was associated with a Breslow thickness > 2 mm [odds ratio (OR) 2·6, 95% confidence interval (CI) 1·4–4·9; P = 0·004)] and > 4 mm (OR 3·6, 95% CI 1·7–7·9; P = 0·001), TMR > 5 per mm 2 (OR 4·5, 95% CI 1·4–13·7; P = 0·009), SLN involvement (OR 2·3, 95% CI 1–5·7; P = 0·038) and tumour stages III–IV (vs. I–II) (OR 3·4, 95% CI 1·6–7·4; P = 0·002), after adjusting for age, sex, obesity, alcohol intake and smoking habits. No significant associations emerged between glycated haemoglobin levels, metformin treatment and melanoma aggressiveness. Conclusions: T2DM, rather than glycaemic control and metformin treatment, is associated with increased cutaneous melanoma aggressiveness at diagnosis.